Escalation of Transportation Service Quality at the Angkoetan Motor Repoeblik Indonesia (Damri) Surabaya - Irawan Irawan; Pudji Astuti; Eka Setyowati (Jurnal Indonesia Sosial Teknologi, 2024)
The development of the times encourages the community to focus on the advancement of science and technology, to create optimal public services. Transportation is one of the sectors that is greatly affected by technological advances. The escalation of people's mobility demands has led to an increase in very significant means of transportation that are not proportional to the number of existing vehicles, resulting in congestion on the streets. Given the importance of the role of transportation, the government needs to provide mass transportation services that are by the needs of services that are regular, safe, comfortable, fast, precise, and affordable. This study uses a qualitative descriptive approach through observation, direct interviews, and documentation to collect data. The goal is to collect detailed information on improving the quality of DAMRI transportation services and analyze the factors that support and hinder these services. The results of the study show that the escalation of DAMRI service quality focuses on the Minimum Service Standards for Road-Based Mass Transportation, namely security, safety, comfort, affordability, equality, and order.